A Flexible and Degradable Hybrid Mineral as a Plastic Substitute. Issue 9 (24th January 2022) - Yu, Yadong; Guo, Zhengxi; Zhao, Yueqi; Kong, Kangren; Pan, Haihua; Xu, Xurong; Tang, Ruikang; Liu, Zhaoming
Abstract: The development of environmentally friendly plastics is critical to ensure sustainable development. In contrast to polymer plastics derived from petrochemicals, inorganic minerals, which are the most abundant matter in Earth's crust, are environmentally friendly. However, the brittleness of these minerals limits their applications as plastics. Here, because of the advantages of both biomineralization and inorganic ionic polymerization, the calcium phosphate (CaP, a typical geological and biological mineral) oligomers are used for biomimetic mineralization under the regulation of polyvinyl alcohol and sodium alginate, resulting in flexible CaP nanofibers with periodic structural defects. The assembly of CaP nanofibers produces a hierarchically structured bulk hybrid mineral (HM), which overcomes the intrinsic brittleness of minerals and exhibits plasticity characteristics. HM exhibits better hardness and thermostability than classical polymer plastics due to its dominant mineral composition. Notably, HM is environmentally friendly and degradable in nature, as it can potentially participate in geological cycles, indicating that this material is an optimal plastic substitute. The construction of periodic structural defects within flexible minerals expands the current understanding of materials science. Abstract : Inspired by biomineralization, a flexible and degradable hybrid mineral (HM), which is dominated by minerals, is constructed by the inorganic ionic polymerization of calcium phosphate ionic oligomers under biomimetic control from organic templates (polyvinyl alcohol and sodium alginate). The HM shows potential to serve as a plastic substitute owing to its superior mechanical properties and environmental friendliness.